Optimal planning of multi-micro grids based-on networks reliability - Guo Wang; Qinqin Wang; Zhi Qiao; Jiuhui Wang; Simon Anderson (Energy Reports, 2020)
Traditional electrical grid as the largest and most complex industry in the world is currently under fundamental development. According to the IEEE Std1547.4, large distribution systems can be clustered into a number of micro-grids (MGs) to facilitate the control and operation infrastructure in future distribution systems. A distribution network with distributed energy resources serving a group of loads, can be operated as a MG, in grid-connected or isolated grid modes. Most recently, the concept of MGs has become an important subject in smart grid area, demanding a systematic method for their optimal planning. The prosperous development of the micro-grid concept implies the definition of an appropriate regulation for its integration on distribution systems. The MG operators are responsible for a reliable energy supply to their consumers. MG formation represents a suitable solution for uninterrupted supplying of critical loads, in the absence of network. In this study, a systematic approach is presented for optimal construction of micro-grid. The problem is solved in two stages. In the first stage, the network is designed as an integrated and active distribution network considering the importance of reliability by using Backward-forward load flow. Next, the distribution network is designed to be divided in to several MGs in order to minimize the cost of electricity generation, improve reliability and voltage profile. In the presented study, stochastic models are considered for representing generation availability related to wind energy and solar energy. The generated power of distributed generation resources such as wind turbines and photovoltaic, have been modeled per hours of the day and the amount of important network parameters are obtained from the results of probabilistic load flow. Practical and important factors such as problem solving space reduction, load controllability, load priority, bus voltage limitation, line capacity limitation and the possibility of forming larger micro-grids by connecting switches between the obtained initial MGs from the first stage are considered in the proposed method. The proposed methodology is implemented for a standard 69-bus distribution system by applying the Imperialist Competitive Algorithm (ICA) in MATLAB software. Results verify the usefulness of the proposed approach in transforming an existing radial distribution network into several autonomous MG.
Keywords: 330; Uncertainty; Distributed generators; Micro-grid; Probabilistic modeling; Smart distribution grids